Deintensified Chemoradiotherapy for Pretreatment Epstein-Barr Virus DNA-Selected Low-Risk Locoregionally Advanced Nasopharyngeal Carcinoma: A Phase II Randomized Noninferiority Trial. Issue 11 (10th April 2022) - Li, Xiao-Yun; Luo, Dong-Hua; Guo, Ling; Mo, Hao-Yuan; Sun, Rui; Guo, Shan-Shan; Liu, Li-Ting; Yang, Zhen-Chong; Yang, Jin-Hao; Qiu, Fang; Sun, Xue-Song; Wang, Pan; et al.
Abstract : PURPOSE: Cumulative doses of 200 mg/m 2 for concurrent cisplatin (DDP) were indicated by retrospective studies as sufficient in conferring survival benefit for locoregionally advanced nasopharyngeal carcinoma (LA-NPC). We performed an open-label, phase II, randomized, controlled trial to test the noninferiority of a two-cycle 100 mg/m 2 concurrent DDP regimen over three-cycle in patients with low-risk LA-NPC with pretreatment Epstein-Barr virus DNA levels < 4, 000 copies/mL. PATIENTS AND METHODS: Eligible patients were randomly assigned 1:1 to receive two cycles or three cycles concurrent DDP-based chemoradiotherapy. The primary end point was 3-year progression-free survival (PFS). The secondary end points included overall survival, distant metastasis-free survival, locoregional relapse-free survival, etc. RESULTS: Between September 2016 and October 2018, 332 patients were enrolled, with 166 in each arm. After a median follow-up of 37.7 months, the estimated 3-year PFS rates were 88.0% in the two-cycle group and 90.4% in the three-cycle group, with a difference of 2.4% (95% CI, –4.3 to 9.1, P noninferiority = .014). No differences were observed between groups in terms of PFS, overall survival, and the cumulative incidences of locoregional relapse and distant metastasis. Patients in the three-cycle group developed significantly more grade 3-4 mucositis (41 [24.8%] v 25 [15.1%]), hyponatremia (26 [15.8%] v 14 [8.4%]), and dermatitis (9 [5.5%] v 2 [1.2%]). The overall all-grade and grade 3-4 toxicity burdens were heavier in three-cycle group (T-scores, 12.33 v 10.57, P < .001 for all grades; 1.76 v 1.44, P = .05 for grade 3-4). Patients in the three-cycle group also showed more all-grade hearing impairment, dry mouth and skin fibrosis, and impaired long-term quality of life. CONCLUSION: Intensity-modulated radiotherapy plus two cycles of concurrent 100 mg/m 2 DDP could be an alternative treatment option for patients with low-risk LA-NPC. Abstract :